PENGARUH PEMBERIAN FRAKSI ETIL ASETAT DAUN TUMBUHAN AKAR KAIK-KAIK (Uncaria cordata (Lour.) Merr.) TERHADAP KADAR Low Density Lipoprotein (LDL) TIKUS PUTIH (Rattus novergicus) JANTAN: The Effect of Giving Ethyl Acetate Fraction of Leaves from Uncaria cordata on Levels of LDL of Male White Rats - Meiriza Djohari; Fina Aryani; Haniyah Nabilah (JURNAL FARMASI DAN MAKANAN, 2025)
Akar Kaik-kaik (Uncaria cordata (Lour.) Merr) can be used as herbal medicine to decrease LDL level in the body. This research aims to determine the effect of ethyl acetate fraction the leaf of akar kaik-kaik (Uncaria cordata (Lour.) Merr) toward LDL level in a male white rat serum (Rattus norvegicus). The measurement method used is Direct Homogeneous Assay using reagents and photometer (Mindray® BA-88A) at a wave length of 578 nm. The results obtained in the form of LDL levels and analyzed using two-way ANOVA. The results showed that the ethyl acetate fraction in the leaves of akar kaik-kaik (Uncaria cordata (Lour.) Merr.) doses of 200 and 400 mg/KgBW kgBW could reduce LDL levels as seen from the significant difference (p<0.05) with the negative control group. and has a comparable effectiveness with atorvastatin seen from the absence of significant differences (p>0.05) with the positive control group.